A comparative study on online marketing between Airasia and Malaysian Airline System (MAS): the perspective of Unimas's Staff / Noridah Adenan - Adenan, Noridah (2007)
The aim of this study is to identify the perspectives of UNIMAS's staffs on the criteria for purchasing airline tickets with respect to AirAsia and Malaysian Airline System (MAS). The study is also to determine the quality of the website provided by AirAsia and MAS and their impact towards customer satisfaction. There were six sections in this study which are the background of the respondent, privacy, trustwortiness, website design/content, communication and level of customer satisfaction. The study was conducted based on the survey by using the questionnaire. Ninty-three sets of questionnaires were distributed amongst the Unimas students. The frequency test and T-test were employed to analyze the data and shown that only two sub-variables in trustworthiness were significance in terms of the website quality provided by AirAsia and MAS. Based on the findings, recommendation were made to improve the quality and services of their website to convince the customer to purchase online in the future.